Typification of some names in the genus Sesleria (Poaceae) - Alonso, Alicia; Acedo, Carmen; Di Pietro, Romeo; Iamonico, Duilio; Llamas, Félix (Phytotaxa, 2016)
As part of the nomenclatural revision of the genus Sesleria (Poaceae), we have found that some names are still untypified. Thus, we have carried out a nomenclatural investigation which led to the designation of five lectotypes (for the names Festuca argentea, Cynosurus cylindricus, Sesleria argentea var. hispanica, S. elongata, and S. sphaerocephala), three epitypes (F. argentea, S. elongata, and S. sphaerocephala) and one neotype (S. autumnalis). Concerning S. insularis a depth discussion was provided and this name was accepted to be lectotypified by Ujhelyi in a double-step typification. All the proposed types are in agreement with the current use of the names, and contribute to stabilize the nomenclatural framework of the genus.